2018
DOI: 10.1111/1365-2745.12933
|View full text |Cite
|
Sign up to set email alerts
|

Community‐level flammability declines over 25 years of plant invasion in grasslands

Abstract: Abstract1. Exotic plant invasions can alter fire regimes in plant communities. Invaders often possess traits that differ from native plants in the community, resulting in increases or declines in community-level flammability, changing fire regimes and potentially causing long-term modifications to plant community composition. Although considering traits of multiple invaders and native species together is useful to better understand how invasions change community-level flammability, few studies have done this.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 50 publications
(121 reference statements)
1
36
1
Order By: Relevance
“…The maximum temperature of flames during burning was measured using an infrared laser thermometer (Fluke 572; Fluke Corp., Everett, WA, USA) to represent combustibility. Samples that failed to ignite were given a value of 150°C, representing the grill temperature (Padullés Cubino et al ., 2018; Wyse et al ., 2018). Sustainability was measured as the period of time that a sample burned (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The maximum temperature of flames during burning was measured using an infrared laser thermometer (Fluke 572; Fluke Corp., Everett, WA, USA) to represent combustibility. Samples that failed to ignite were given a value of 150°C, representing the grill temperature (Padullés Cubino et al ., 2018; Wyse et al ., 2018). Sustainability was measured as the period of time that a sample burned (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The components of flammability are typically considered to be combustibility (associated metrics are rate of consumption, flame temperature and flame height), ignitability (time to ignition), sustainability (time to flame extinction and residence time) and consumability (proportion of mass consumed) [5][6][7]. In addition, fuel load (above-ground biomass) is a key driver of whole-plant combustibility and sustainability [8,9] and is central to understanding community-and landscape-scale flammability.…”
Section: Introductionmentioning
confidence: 99%
“…While several studies have estimated plant and community flammability at individual-, ecosystem-, or biome-level by measuring shoot-level flammability (e.g. Burger & Bond, 2015;Calitz, Potts, & Cowling, 2015;Jaureguiberry et al, 2011;Padullés Cubino, Buckley, Day, Pieper, & Curran, 2018;Wyse et al, 2016), few have quantitatively assessed trait-flammability relationships. Calitz et al (2015) compared ordinal trait values, including leaf size, leaf texture, leaf density and twigginess (number of twigs per unit volume), to shoot flammability, and found that plants with small leaves and high twigginess had relatively high flammability.…”
mentioning
confidence: 99%